Water for life making it happen (World Health Organization : UNICEF, 2005)
This Web site is part of a large online resource designed to provide visitors with access to World Health Organization and UNICEF publications. This particular document is a 2005 report on water supply and sanitation for the next ten years. Discover how sufficient and better quality drinking water and basic sanitation can dramatically save lives and speed the achievement of all eight Millennium Development Goals (MDGs).